Labeling and preliminary in vivo evaluation of the 5-HT7 receptor selective agonist [11C]E-55888. Issue 9 (1st May 2015) - Hansen, Hanne D.; Andersen, Valdemar L.; Lehel, Szabolcs; Magnussen, Janus H.; Dyssegaard, Agnete; Stroth, Nikolas; Kristensen, Jesper L.; Knudsen, Gitte M.; Herth, Matthias M.
Graphical abstract